How open- and closed skills athletes adapt decisions to an uncertain environment with and without a stressful condition - Russo, G.; Ottoboni, G.; Farnè, M.; Ceciliani, A.; Tessari, A. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
Introduction: Athletes must decide their actions under stressful situations. These abilities could also be transferred into a general domain (1, 2). Thus, the present research analyzed the decision-making processes of athletes in an uncertain environment and how they acted when exposed to stressful situations.